Phenotypic and molecular characterization of HA-MRSA in Taif hospitals, Saudi Arabia - Emad M Eed; Mabrouk M Ghonaim; Yousry M Hussein; Taiser M Saber; Amany S Khalifa (Journal of Infection in Developing Countries)
Introduction: Methicillin-resistant S. aureus (MRSA) is one of the most important organisms causing hospital-acquired infections worldwide. Molecular analysis of MRSA strains from Taif, Saudi Arabia, had not been previously done. Phenotypic and molecular characteristics of MRSA isolated from Taif hospitals were investigated. Methodology: This study involved S. aureus strains isolated from different clinical samples from Taif hospitals. MRSA strains were identified and antimicrobial susceptibility profiles were determined. Multiplex polymerase chain reaction (PCR) was used to identify S. aureus-specific sequence, mecA genes, and type of staphylococcal cassette chromosome mec (SCCmec). MRSA strains were typed using coagulase gene polymorphism. Results: In total, 390 strains of S. aureus were isolated, and 58 MRSA strains – 40 hospital-acquired  MRSA (HA-MRSA) and 18 community-acquired MRSA (CA-MRSA) – were detected. HA-MRSA strains included three SCCmec types, while CA-MRSA strains included two SCCmec types. PCR amplification and restriction of the coagulase gene of the 58 MRSA isolates showed nine different patterns, while three strains were non-typable. HA-MRSA strains showed seven distinct restriction fragment length polymorphism (RFLP) patterns; the most frequent was pattern 2 (15 isolates), followed by patterns 1 and 4 (5 isolates each). CA-MRSA showed five RFLP patterns; the most frequent was pattern 3 (7 isolates) followed by pattern 8 (6 isolates). Conclusions: HA-MRSA strains were more common than CA-MRSA strains. SCCmec typing and coagulase gene polymorphism analysis may be useful methods for studying clonal relatedness of isolates and for discriminating between HA-MRSA and CA-MRSA.